Gamificação e leitura: em jogo, a formação de jovens adultos - Amaral, Joseane (2019)
The task of recognizing new spaces and approaches amid the hybrid languages of the internet prompted us to start the present investigation in the reading research field. This thesis proposes to consider gamification in technological supports, linked to reading experiences (Larrosa, 2012) in the process of training young adult readers. Therefore, we verified similarities and distinctions in the ways of conceptualizing the phenomenon, especially from the researchers Pelling (2014), Deterding (2012), Werbach and Hunter (2012) and Burke (2015), exponents in this field of studies. Allied to this verification is the analysis of mobile applications intended for online reading, interpreted with regard to their constitution and presence of game elements, based on gamification theories. In order to spread gamification as a concept and presumed learning methodology, we try to bring two apparently antagonistic poles together: digital gaming - seen in its recreational and spontaneous aspect, the true paidia (Caillois, 2001); and reading, associated with quiet and thoughtful practices (Chartier, 1999). Our investigation is characterized as netnographic research (Kozinets, 2014), seeking to incorporate the influence of the internet in the various social worlds of contemporary times; and as a methodological course of wanderings (Santaella, 2004) fed by the pleasure of the discoveries. From the approach between reading and game culture we seek to extract important discoveries in language studies, answering the challenges imposed by hypermodernity society. As a result we intent to extract new findings in language studies, considering interactions between reading experiences and game culture, answering the challenges imposed by hypermodernity society.